Measurement of Quality of Life IV. Use of the SEQOL, QOL5, QOL1, and Other Global and Generic Questionnaires - Soren Ventegodt; Joav Merrick; Niels Jorgen Andersen (The Scientific World Journal)
Quality-of-life (QOL) rating scales can be used to measure and describe the quality of life of a specific population or patient group. Many decisions can be taken and policies implemented when we know more about a group or population. The global quality-of-life concept may help in expressing the objective of the initiatives taken to benefit specific groups. The objective may be that we hope the efforts will increase their quality of life by a certain percentage. This explicit expectation will force the decision makers to stand by their noble intentions. They are obliged to evaluate their efforts and will have to learn something from it.A questionnaire thus constitutes a useful scientific instrument, as databases based on comprehensive and thorough questionnaire surveys that seek to encompass all aspects of life can provide valuable and precise information. The value of such a database depends on the correct use of the questionnaires and this paper examines some examples of how quality-of-life rating scales can be used.We identified at least ten ways to use the quality-of-life questionnaire: describing the quality of life of a population or patient group; formulating an objective for support, treatment, or care; screening or identifying individuals who need treatment; evaluating treatment and care; facilitating communication between physician and patients; involving the patient in the decision-making process; allocating resources; investigating the causal relation between the quality of life and ill health in prospective studies; creating an awareness of the quality of life and health promotion; and helping the practitioner to accumulate knowledge.Enhancing the quality of life is therefore a determining factor in the process of increasing awareness and responsible conduct in relation to the environment, natural resources, the working environment, and the structure of society. Putting the quality of life on the agenda inherently has a constructive and positive effect on the life and functioning of the individual and society.